"Educar para a vida e não para a escola”: a educação desejada nos congressos internacionais de surdos entre 1889 e 1900 - Rodrigues, José Raimundo (2023)
This thesis is based on a Foucauldian approach utilizing the author’s concepts of tools of resistance and counter-conducts. It presents an analysis of the kind of education the deaf wished for themselves, and how this was expressed discursively in the international congresses they organized in the late nineteenth century. It is a documentary research whose corpus of analysis consists of the reports of the Paris (1889), Chicago (1893), Geneva (1896), Dijon (1898) and Paris (1900) congresses - Section of the deaf community. The general objective is: to understand how education, discursively proposed in the international congresses of deaf people in the late nineteenth century, was considered as resistance/counter-conduct. The specific objectives are: a) to analyze the documents of the congresses produced by the deaf, such as archives and monuments, as the official version of their own desires in terms of deaf education; b) to investigate how documents on deaf education, discursively speaking, proliferated during the congresses of the deaf; c) to discuss how the documents explicitly show the resistance and counter-conducts of the deaf before the kind of education they were offered at that time. The analysis of the material contained in the archives of the series under research allowed us to problematize the traditional narrative about the history of deaf education after the 1880 Milan Congress, as well as fashion a different history protagonised by the deaf themselves. The discursiveness that permeates the meetings and debates also depicts an educated, active, and engaged deaf community who, beyond oppositions concerning methods, had a good understanding of education. Therefore, we defend the thesis that historical research on the education the deaf discursively claimed throughout their congresses of the late nineteenth century suggests an "education for life", a quest for a knowledge that would provide them with an integral formation and make them “re-exist” in the school system. The contribution of the present work to the area of education and, more specifically, to the history of deaf education is to provide an analysis of how the deaf conceived their education in a way that was different from that proposed by their hearing teachers, too much focused on oralisation, that was supported and implemented by the governments of each country then. Thus, the study of material, that had not yet been translated into Portuguese language, concerning events organized by the deaf, gives access to records that strike a resounding echo today, particularly, regarding education.